Microfluidic Assessment of Frying Oil Degradation - Liu, Mei (Sci Rep, 2016)
Monitoring the quality of frying oil is important for the health of consumers. This paper reports a microfluidic technique for rapidly quantifying the degradation of frying oil. The microfluidic device generates monodispersed water-in-oil droplets and exploits viscosity and interfacial tension changes of frying oil samples over their frying/degradation process. The measured parameters were correlated to the total polar material percentage that is widely used in the food industry. The results reveal that the steady-state length of droplets can be used for unambiguously assessing frying oil quality degradation.